Microbial succession in an inflated lunar/Mars analog habitat during a 30-day human occupation. Issue 1 (December 2016) - Mayer, Teresa; Blachowicz, Adriana; Probst, Alexander; Vaishampayan, Parag; Checinska, Aleksandra; Swarmer, Tiffany; de Leon, Pablo; Venkateswaran, Kasthuri
Abstract Background For potential future human missions to the Moon or Mars and sustained presence in the International Space Station, a safe enclosed habitat environment for astronauts is required. Potential microbial contamination of closed habitats presents a risk for crewmembers due to reduced human immune response during long-term confinement. To make future habitat designs safer for crewmembers, lessons learned from characterizing analogous habitats is very critical. One of the key issues is that how human presence influences the accumulation of microorganisms in the closed habitat. Results Molecular technologies, along with traditional microbiological methods, were utilized to catalog microbial succession during a 30-day human occupation of a simulated inflatable lunar/Mars habitat. Surface samples were collected at different time points to capture the complete spectrum of viable and potential opportunistic pathogenic bacterial population. Traditional cultivation, propidium monoazide (PMA)–quantitative polymerase chain reaction (qPCR), and adenosine triphosphate (ATP) assays were employed to estimate the cultivable, viable, and metabolically active microbial population, respectively. Next-generation sequencing was used to elucidate the microbial dynamics and community profiles at different locations of the habitat during varying time points. Statistical analyses confirm that occupation time has a strong influence on bacterial community profiles. The Day 0 samples (before human occupation) have a very different microbial diversity compared to the later three time points. Members ofProteobacteria (esp.Oxalobacteraceae andCaulobacteraceae ) andFirmicutes (esp.Bacillaceae ) were most abundant before human occupation (Day 0), while other members ofFirmicutes (Clostridiales ) andActinobacteria (esp.Corynebacteriaceae ) were abundant during the 30-day occupation. Treatment of samples with PMA (a DNA-intercalating dye for selective detection of viable microbial population) had a significant effect on the microbial diversity compared to non-PMA-treated samples. Conclusions Statistical analyses revealed a significant difference in community structure of samples over time, particularly of the bacteriomes existing before human occupation of the habitat (Day 0 sampling) and after occupation (Day 13, Day 20, and Day 30 samplings).Actinobacteria (mainlyCorynebacteriaceae ) andFirmicutes (mainlyClostridiales Incertae Sedis XI andStaphylococcaceae ) were shown to increase over the occupation time period. The results of this study revealed a strong relationship between human presence and succession of microbial diversity in a closed habitat. Consequently, it is necessary to develop methods and tools for effective maintenance of a closed system to enable safe human habitation in enclosed environments on Earth and beyond.